THE RELATIONSHIP BETWEEN MATERNAL PARITY AND PERINEAL RUPTER INCIDENCE IN NORMAL DELIVERY AT PMB MINARTI, Amd. b. TRAWASAN VILLAGE KEC. SUMOBITO REGENCY. JOMBANG - Sabrina Dwi Prihartini; Vivin Eka Rahmawati; Ninik Azizah; Ruwaidadul Wardah (Bajang Institute, 2021)
Childbirth is one of the efforts to start the birth process, most of the births involve the birth canal, one part of the birth canal is the perineum. In labor parity also affects the incidence of perineal rupture, in parity or primiparous mothers there is a greater risk of experiencing perineal tears than mothers with multipara parity. This study aims to determine the relationship between maternal parity and the incidence of perineal rupture in normal delivery at PMB Minarti, Amd.Keb. Trawasan Village, Kec. Sumobito Kab. JombangThe research design used in this study is a survey research method with an approachcroos sectional which describes the relationship between maternal parity and the incidence of perineal rupture in normal delivery. Respondents who were given treatment consisted of 18 people who were divided into two. They are primiparas and multiparas. Measuring tool used by direct observation with patients. Research observations using the hypothesis test used in this study areUji Chi SquareWhich counted manually and SPSS with a significant level value of 0.05 (Alpha). The results of the study stated that from the primipara group there were 9 people who experienced perineal rupture, 8 people who did not experience perineal rupture, 1 person. Meanwhile, from the multiparous group, there were 9 people who experienced perineal rupture, 3 people and 6 people who did not experience rupture. Based onuji chi squarein SPSS the result is that x2 count < significant level or 0.016 < 0.05 then HI is accepted, which means that there is a parity relationship with the incidence of perineal rupture in normal delivery. The conclusion from the data above is that there is a relationship between normal delivery between maternal parity and the incidence of perineal rupture at PMB Minarti, Amd.Keb. Therefore, it is recommended for midwives to provide good and professional midwifery care and care for mothers.